Perception on Psychiatric Care Received by Patients Admitted Following Deliberate Self Harm to Three Hospitals in Galle District - Chandrasiri, P. A. A.; Gunethunga, W.; Rajapakshe, H. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2019)
Deliberate Self-harm (DSH) adds a significant burden to the health care system in Sri Lanka. Delivering appropriate psychiatric care is crucial to minimize further risk. The objective of this study was to describe perception on psychiatric care received by patients who are admitted following DSH to selected hospitals in Galle District. Sample was taken from a large study which was intended to describe psychiatric management of patients admitted following DSH to 3 tertiary care hospitals in the Southern province of Sri Lanka. Only a sub-sample of 60 patients was taken for the analysis and it was further supplemented with a qualitative component. An interviewer-administered questionnaire (IAQ) was used and a series of in-depth interviews were also conducted. Descriptive statistics were calculated and qualitative data was analyzed separately. As per the results, only 22 (36.7%) were referred to the psychiatry unit and the rest were discharged only after managing their medical problems. A majority (68.2%) told that they were not informed about the need and importance of psychiatric referral. But a larger proportion mentioned that it was good (54.5%) and it brought some relief to them (81.8%). Only a few acknowledged that it helped them to solve their problems (22.7%) and only a very few (13.6%) told that they were embarrassed because of referring to the psychiatry unit. Out of those who had psychiatric referral, only 59.0% were requested to attend for clinic follow up. But only 41.6% intended to come. Upon inquiring about their overall perception about psychiatric referral, almost all gave positive remarks. However, results of this study can be used a baseline and further studies are needed to confirm burden issue related to the health care system in Sri Lanka.
Keywords: Deliberate Self Harm, Psychiatric Care